Shifting Communication through Virtual Influencers Driven Metaverse Revolution - Saman, Michel Gougou (Journal of Communication and Public Relations, 2025)
The metaverse revolution and the shifting to artificial intelligence (AI) are transforming human daily activities with the growth of chatbots and virtual agents changing communication and public relations strategies. Therefore, this paper aims to explore and question virtual influencers in Africa regarding communication strategies in organizations and human daily activities according to the metaverse revolution. This explorative qualitative descriptive research adopted a synthesis review of scientific publications and online investigation on two virtual influencers pages on Instagram in Africa to collect the data according to the influencers marketing paradigm on social media. First, the findings underlined the social presence, parasocial connectedness and perceived credibility of these virtual AI influencers in the innovative usages to support marketing and communication. Then, the results underlined the prospective application of AI virtual influencers and ethical issues in communication and public relations strategies. As a recommendation, the integration of AI Virtual influencers and AI agents in human activities requires to update the skills of managers and users by considering a human-centered approach according to the industry 5.0 paradigm.